BEHAVIORAL PROGRAMS FOR TYPE 2 DIABETES MELITUS: A SYSTEMATIC REVIEW - Andreria Hatulely, Chrysman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. It is possible that behavioral programs can improve outcomes for people living with type 2 diabetes mellitus; however, there is a huge variety of behavioral interventions to choose from, and it is unclear how to maximize the efficacy of these programs.The aim: This article discusses osteosynthesis in patients with femoral neck fractures.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 655 articles, whereas the results of our search on SagePub brought up 254 articles. The results of the search conducted for the last year of 2013 yielded a total 192 articles for PubMed and 89 articles for SagePub. In the end, we compiled a total of 33 papers, 21 of which came from PubMed and 12 of which came from SagePub. We included seven research that met the criteria.Conclusion: Non-pharmacological interventions that can be carried out are complementary therapies such as controlling eating patterns, doing relaxation and regular physical activity. Exercise is a strong stimulus to increase glucose input (glucose uptake) into muscle cells.